Failure to recognize preoperatively high-risk endometrial carcinoma is associated with a poor outcome. (November 2015) - Di Cello, Annalisa; Rania, Erika; Zuccalà, Valeria; Venturella, Roberta; Mocciaro, Rita; Zullo, Fulvio; Morelli, Michele
Abstract: Objective: To evaluate the misdiagnosis between endometrial biopsy and definitive surgical pathology and to assess whether the failure in recognizing preoperatively high-risk endometrial carcinoma (EC) can impact oncological outcomes. Study design: A retrospective study was conducted to evaluate patients with EC diagnosed by preoperative endometrial biopsy who subsequently underwent surgical staging between 2006 and 2013 at our institution. In patients with a surgical diagnosis of high-risk EC, histotype and grade change between the endometrial biopsy and surgical specimen (discordance diagnosis) were evaluated and correlated to survival outcomes. Cox's regression model for multivariable analysis was used to evaluate the effect of several variables (age, stage, discordance in diagnosis, co-morbidities, frozen section, extensive surgical staging and adjuvant chemotherapy) on the survival rate. Results: Data from 447 patients were reviewed. Among 109 women with surgical diagnosis of high-risk EC, 35 (32.1%) were preoperatively misdiagnosed. Of these 35 women, 24 (68.6%) cases were upgraded to grade 3, and 11 (3.4%) were upgraded to serous or clear cell type in the definitive specimen. The 5-year overall survival (OS; 70.2 vs. 86.8%; p  = 0.029), disease-specific survival (DSS; 72.5 vs. 88.2%; p  = 0.039) and recurrence free survival (RFS; 62.6 vs. 82.5%; p  = 0.024) were significantly lower in the high-risk EC patients who were preoperatively undiagnosed in the endometrial biopsy compared with patients with an appropriate preoperative histological diagnosis. Controlling for age, stage, co-morbidities, frozen section, extensive surgical staging and adjuvant chemotherapy, multivariable analysis revealed that discordance in diagnosis was associated with poorer survival outcomes. Conclusion: Failure to recognize preoperatively high-risk ECs is associated with worse outcomes.